Management of fishing port at Tiku, Agam regency, west Sumatra province - Nova Fatma Hatta; Jonny Zain; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A series survey activity was carried out on March 23th to April 3rd, 2013 at fishingport in Tiku village. Purpose of this study is to investigate the implementation ofmanagement theory at fishing port. The result shows that the management theory in fishingport has not been well conducted. This conditions was caused less of personal staff (4persons), as well as the Standard Operational Procedure (SOP) was not applied and norulesgoverning thearrivalanddeparture of the fishing boat. The fishing port facilities werenot used, such as cold storage, fresh water tank, and fish landing.Keywords: Fishing port, management, standard operational procedure (SOP), Tiku